Bank Business Model Migrations in Europe: Determinants and Effects. (2nd November 2020) - Ayadi, Rym; Bongini, Paola; Casu, Barbara; Cucinelli, Doriana
Abstract: In response to post‐crisis regulatory reforms, the European banking sector has undergone significant changes that have led banks to reconsider their strategies, structures and operations. Based on a sample of over 3, 000 banks from 32 European countries during the period 2010–2017, we identify banks' business models based on cluster analysis and track their evolution. We then apply a logistic regression and find that banks with higher risk and lower profitability are more likely to change their business model. Employing a propensity score matching approach, we investigate the effect of migration on bank performance and find that changing the business model affects banks positively (i.e. migrating banks increase their profitability, stability and cost efficiency). The effect of migration differs depending on the target business model. When switches are a consequence of being acquired or motivated by regulatory compliance, the positive impact remains.